Implementasi Cooperative Learning Tipe Numbered Head Together (NHT) untuk Meningkatan Hasil Belajar Subtema Usaha Pelestarian Lingkungan di Kelas V SDN Gisikdrono 01 Kota Semarang - Suwarti, Sri (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
This classroom action research is based on thematic learning in class V of SDN Gisikdrono 01 Semarang City. Based on the teaching experience carried out by researchers, it is known that several factors are assumed to be the cause of low thematic learning outcomes, namely a) Subject matter that is still considered difficult for children. b) The learning process is less interesting, c) students only rely on memorization without knowing how to read correctly. Judging from the completeness of students' learning with KKM 70 in several daily tests on the business sub-theme around me last year, of the 27 students, only 11 completed and 16 did not complete, the students' incompleteness lies in the students' inability to understand the material in the sub-theme. the body's way of processing clean air from the respiratory system in humans. The problem of low results must be addressed immediately and teachers need to reflect on their performance. Efforts to improve learning outcomes. Efforts to improve thematic learning outcomes in the sub-theme of environmental conservation efforts, including through Numbered Head Together (NHT) type cooperative learning, including through NHT type cooperative learning. The results of the research show that there are thematic learning outcomes for the sub-theme of environmental conservation efforts using the NHT type cooperative learning model in Class V students at SDN Gisikdrono 01 Semarang City, even semester of the 2022/2023 school year, this can be seen from the increase per cycle, where pre-cycle there were 12 students or 44.4% who experienced an increase in cycle I, namely there were 17 students or 63.0% and in cycle II there were 22 students or 81.5%. An increase also occurred in students' learning activity, where in cycle I there were 16 students or 59%, there was an increase in cycle II, namely there were 23 students or 85%, which was in accordance with the specified indicators, namely 80%.